Pathogenicity of Human ST23 Streptococcus agalactiae to Fish and Genomic Comparison of Pathogenic and Non-pathogenic Isolates - Wang, Rui; Li, Liping; Huang, Yin; Huang, Ting; Tang, Jiayou; Xie, Ting; Lei, Aiying; Luo, Fuguang; Li, Jian; Huang, Yan; Shi, Yunliang; Wang, Dongying; et al. (Frontiers in Microbiology, 2017)
Streptococcus agalactiae, or Group B streptococcus (GBS), is a major pathogen causing neonatal sepsis and meningitis, bovine mastitis, and fish meningoencephalitis. CC23, including its namesake ST23, is not only the predominant GBS strain derived from human and cattle, but also can infect a variety of homeothermic and poikilothermic species. However, it has never been characterized in fish. This study aimed to determine the pathogenicity of ST23 GBS to fish and explore the mechanisms causing the difference in the pathogenicity of ST23 GBS based on the genome analysis. Infection of tilapia with 10 human-derived ST23 GBS isolates caused tissue damage and the distribution of pathogens within tissues. The mortality rate of infection was ranged from 76% to 100%, and it was shown that the mortality rate caused by only three human isolates had statistically significant difference compared with fish-derived ST7 strain (P < 0.05), whereas the mortality caused by other 7 human isolates did not show significant difference compared with fish-derived ST7 strain. The genome comparison and prophage analysis showed that the major genome difference between virulent and nonvirulent ST23 GBS was attributed to the different prophage sequences. The prophage in the P1 region contained about 43% GC and encoded 28-39 proteins, which can mediate the acquisition of YafQ / DinJ structure for GBS by phage recombination. YafQ / DinJ belongs to one of the bacterial toxin–antitoxin (TA) systems and allows cells to cope with stress. The ST23 GBS strains carrying this prophage were not pathogenic to tilapia, but the strains without the prophage or carrying the pophage that had gene mutation or deletion, especially the deletion of YafQ/DinJ structure, were highly pathogenic to tilapia. In conclusion, human ST23 GBS is highly pathogenic to fish, which may be related to the phage recombination.